2018
DOI: 10.14238/pi58.3.2018.106-9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and frequency of pediatric congenital heart disease at the Cardiac Research Institute of Kabul Medical University, Afghanistan

Abstract: Background Congenital heart disease (CHD) is the most

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Our results are in comparison with a study which reported almost the same proportions of acyanotic and cyanotic CHD in their pediatric population. 15 Among acyanotic CHD patients we observed that Ventricular Septal Defect was seen in 31.5% patients, Atrial Septal Defect was seen in 48.8% patients, VSD+ASD was seen in 8.7% patients while Patent Ductus Arteriosus was seen in 11% patients. In patients with cyanotic CHD Tetralogy of Fallot was seen in 40.9% patients, Transposition of great arteries + VSD was seen in 15.9% patients, Tricuspid atresia was seen in 29.5% patients while Total Anomalous Pulmonary Venous Connection was seen in 13.6%.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results are in comparison with a study which reported almost the same proportions of acyanotic and cyanotic CHD in their pediatric population. 15 Among acyanotic CHD patients we observed that Ventricular Septal Defect was seen in 31.5% patients, Atrial Septal Defect was seen in 48.8% patients, VSD+ASD was seen in 8.7% patients while Patent Ductus Arteriosus was seen in 11% patients. In patients with cyanotic CHD Tetralogy of Fallot was seen in 40.9% patients, Transposition of great arteries + VSD was seen in 15.9% patients, Tricuspid atresia was seen in 29.5% patients while Total Anomalous Pulmonary Venous Connection was seen in 13.6%.…”
Section: Discussionmentioning
confidence: 79%
“…Openepi was used to calculate the sample size, we took previous frequency of 20% 15 cyanotic CHD, 6% margin of error and 95% confidence interval, the calculated sample size was 171. Statistical Analysis was performed using SPSS software for categorical and numerical data.…”
Section: Methodsmentioning
confidence: 99%